Evaluation of the implementation of electronic medical records in Lubuk Buaya Padang Public Health Center in 2023 - Dewi Oktavia; Annisa Wahyuni (Jurnal Mantik, 2023)
The importance of electronic medical records aims to improve the quality of health services, provide legal certainty in the administration and management of medical records, guarantee the security, confidentiality, integrity and availability of medical record data; and realizing the implementation and management of digital-based and integrated Medical Records. Based on the results of observations in the field, several community health centers in Padang City conducted comparative studies with the Lubuk Buaya Community Health Center. This public health center is an example of a community health center that has implemented electronic medical records. This research aims to evaluate the use of electronic medical records at the Lubuk Buaya Padang Public Health Center in 2023. The research method uses a quantitative approach with the Performance, Information, Economic, Control, Efficiency, Service (PIECES) method. Sampling was carried out using a total sampling technique. Research data was collected by distributing questionnaires regarding the use of electronic medical records. The results of the variable or dimensional analysis show that the aspects with an average level of satisfaction for each performance are 3.76 (satisfied), information is 3.67 (satisfied), economics is 3.75 (satisfied), Control is 3.11 (doubtful), efficiency is 3.86 , (satisfied) and service 3.89 (satisfied). Of the six dimensions, all answered that they were satisfied with the implementation of electronic medical records except for the Control dimension which was still unsure. It is recommended that the Puskesmas need to improve control aspects so that the implementation of electronic medical records becomes of higher quality